A STUDY ON IMPACT OF VIRTUAL REALITY IN STIMULATING INDIAN STOCK MARKET EDUCATION - Goel, Neha; Nair, Binu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The incorporation of Virtual Reality (VR) and Augmented Reality (AR) technologies in simulating stock market environments has revolutionized investor training. This study examines the prospects of VR and AR tools to create immersive and interactive learning platforms for novice and seasoned investors. By simulating real-time market scenarios, these advancements facilitate experiential learning, enhance comprehension, and minimize the risks associated with direct market participation. The study outlines the current advancements in VR and AR, evaluates their effectiveness in financial education, and identifies challenges to their broader adoption. Recommendations for improving the application of these technologies are also provided. The research concludes by emphasizing the significance of these tools in transforming investor education and outlines future directions for continued exploration and development in this domain.